TaSYP71, a Qc-SNARE, Contributes to Wheat Resistance against Puccinia striiformis f. sp. tritici - Liu, Minjie; Peng, Yan; Li, Huayi; Deng, Lin; Wang, Xiaojie; Kang, Zhensheng (Frontiers in Plant Science, 2016)
N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs) are involved in plant resistance; however, the role of SYP71 in the regulation of plant–pathogen interactions is not well known. In this study, we characterized a plant-specific SNARE in wheat, TaSYP71, which contains a Qc-SNARE domain. Three homologs are localized on chromosome 1AL, 1BL, and 1DL. Using Agrobacterium-mediated transient expression, TaSYP71 was localized to the plasma membrane in Nicotiana benthamiana. Quantitative real-time PCR assays revealed that TaSYP71 homologs was induced by NaCl, H2O2 stress and infection by virulent and avirulent Puccinia striiformis f. sp. tritici (Pst) isolates. Heterologous expression of TaSYP71 in Schizosaccharomyces pombe elevated tolerance to H2O2. Meanwhile, H2O2 scavenging gene (TaCAT) was downregulated in TaSYP71 silenced plants treated by H2O2 compared to that in control, which indicated that TaSYP71 enhanced tolerance to H2O2 stress possibly by influencing the expression of TaCAT to remove the excessive H2O2 accumulation. When TaSYP71 homologs were all silenced in wheat by the virus-induced gene silencing system, wheat plants were more susceptible to Pst, with larger infection area and more haustoria number, but the necrotic area of wheat mesophyll cells were larger, one possible explanation that minor contribution of resistance to Pst was insufficient to hinder pathogen extension when TaSYP71 were silenced, and the necrotic area was enlarged accompanied with the pathogen growth. Of course, later cell death could not be excluded. In addition, the expression of pathogenesis-related genes were down-regulated in TaSYP71 silenced wheat plants. These results together suggest that TaSYP71 play a positive role in wheat defense against Pst.